Trial of hirudotherapy in labial necrosis: A case report - Doğan, Ozan; Çoban, Ulaş; Ayhan, Işıl; Kasapoğlu, Ali; Çalışkan, Eray (Journal of Surgery and Medicine, 2020)
Treatment of a patient who developed post-operative labial necrosis was aimed with hirudotherapy. A Bartholin cyst was excised but because of the size of the cyst, labial asymmetry occurred, therefore, labial reconstruction was performed on the left labium majus. On post-operative Day 2, the labia became ischemic and necrosis began to develop. We applied hirudotherapy, but no difference was observed after the 5th day. Part of necrotic labium spontaneously split from the healthy tissue underneath. Leech therapy has been used for a long time; however, it was approved by FDA in 2004 and it is a very rarely used treatment method in gynecology. There are no guidelines on duration of leech application, and we wanted our case to set an example. In our case, we eventually had to excise the necrotic labium, which may be due to delay or the insufficient length of leech therapy.